Seasonal overturning variability in the eastern North Atlantic subpolar gyre: a Lagrangian perspective - O. J. Tooth; H. L. Johnson; C. Wilson; D. G. Evans (Ocean Science, 2023)
Both observations and ocean reanalyses show a pronounced seasonality in the strength of the Atlantic meridional overturning circulation (MOC) within the eastern North Atlantic subpolar gyre (eSPG). However, attributing this overturning seasonality to seasonal dense water formation remains challenging owing to the wide distribution of recirculation timescales within the Iceland and Irminger basins. Here, we investigate the nature of seasonal overturning variability using Lagrangian water parcel trajectories initialised across the Overturning in the Subpolar North Atlantic Program (OSNAP) East section within an eddy-permitting ocean sea ice hindcast. By adopting a Lagrangian perspective, we show that the seasonal minimum of the Eulerian overturning at OSNAP East in autumn results from a combination of enhanced stratification and increased southward transport within the upper East Greenland Current. This convergence of southward transport within the MOC upper limb is explained by decreasing water parcel recirculation times in the upper Irminger Sea, consistent with a gyre-scale response to seasonal wind forcing. To account for the diversity of recirculation times within the eSPG, we also quantify the Lagrangian overturning (LMOC) as the total dense water formation along water parcel trajectories. The majority of water parcels, sourced from the central and southern branches of the North Atlantic Current, fail to return to OSNAP East prior to experiencing wintertime diapycnal transformation into the lower limb, and thus they determine the mean strength of the LMOC within the eSPG (8.9 ± 2.2 Sv). The strong seasonality of the LMOC is explained by a small collection of upper-limb water parcels, circulating rapidly (≤ 8.5 months) in the upper Irminger and central Iceland basins, whose along-stream transformation is determined by their month of arrival at OSNAP East.